Bringing GC–MS profiling of steroids into clinical applications. Issue 2 (25th June 2014) - Choi, Man Ho; Chung, Bong Chul
<x xml:space="preserve">Abstract</x> Abnormalities of steroid biosynthesis and excretion are responsible for the development and prevention of endocrine disorders, such as metabolic syndromes, cancers, and neurodegenerative diseases. Due to their biochemical roles in endocrine system, qualitative and quantitative analysis of steroid hormones in various biological specimens is needed to elucidate their altered expression. Mass spectrometry (MS)‐based steroid profiling can reveal the states of metabolites in biological systems and provide comprehensive insights by allowing comparisons between metabolites present in cells, tissues, or organisms. In addition, the activities of many enzymes related to steroid metabolism often lead to hormonal imbalances that have serious consequences, and which are responsible for the progress of hormone‐dependent diseases. In contrast to immunoaffinity‐based enzyme assays, MS‐based methods are more reproducible in quantification. In particular, high‐resolution gas chromatographic (GC) separation of steroids with similar chemical structures can be achieved to provide rapid and reproducible results with excellent purification. GC–MS profiling therefore has been widely used for steroid analysis, and offers the basis for techniques that can be applied to large‐scale clinical studies. Recent advances in analytical technologies combined with inter‐disciplinary strategies, such as physiology and bioinformatics, will help in understanding the biochemical roles of steroid hormones. Therefore, comprehensive analytical protocols in steroid analysis for different research purposes may contribute to the elucidation of complex metabolic processes relevant to steroid function in many endocrine disorders, and in the identification of diagnostic biomarkers. © 2014 Wiley Periodicals, Inc. Mass Spec Rev 34: 219–236, 2015.